ANALISIS PENGISIAN BATERAI MENGGUNAKAN SEL SURYA 20 WP - Muhamad Hadi Mainaki; Ain Sahara; Riza Hadi Saputra, A.M; Miftahul Huda (Fakultas Teknik, Universitas Wijayakusuma Purwokerto, 2020)
TodayÂ manyÂ expertsÂ haveÂ discoveredÂ aÂ varietyÂ ofÂ electricÂ powerÂ generationÂ devices,Â whichÂ workÂ by convertingÂ energyÂ intoÂ electricalÂ energy.Â InÂ thisÂ case,Â theÂ geographicalÂ situationÂ inÂ IndonesiaÂ isÂ very supportiveÂ toÂ beÂ ableÂ toÂ developÂ oneÂ alternativeÂ electricityÂ usingÂ sunlight.Â TheÂ alternativeÂ energy application uses the main component, namely